DAYA SAING PEREKONOMIAN INDONESIA : PENGUKURAN DAN STRATEGI - Sugiyanto, FX (JURNAL BISNIS STRATEGI, 2002)
In a global wortd, nations compete ta sustain and increase their standard of living. For this reason, competitiveness is key factor of nation  to compete among them. There are many factors to measure nation com petWveness: economic performance, government efficiency, business efficiency and infrastructure. Each factor can breakdowfl to many criteria. Another factor of level of country's competitiveness determinant is  value system .  As a Max Weber's study, economic development of nations were correlated with culture of their people. Consequently, nations do not compete with products and service alone, but also with education and value systems. In  Indonesian case, there are many problems with economic competitive ness.. Lack of macroeconomic policies, beareucratric regidity, bad governance management and bad corporate  governance management are the major problems to improve economic competitiveness. Democratisation process will be a bridge to achieve high nation competitiveness. Maybe.